Suicidality Among Transgender Youth: Elucidating the Role of Interpersonal Risk Factors - Austin, Ashley; Craig, Shelley L.; D’Souza, Sandra; McInroy, Lauren B. (Journal of interpersonal violence, 2022)
Data indicate that 82% of transgender individuals have considered killing themselves and 40% have attempted suicide, with suicidality highest among transgender youth. Using minority stress theory and the interpersonal theory of suicide, this study aims to better understand suicide risk among transgender youth. The present study examines the influence of intervenable risk factors: interpersonal and environmental microaggressions, internalized self-stigma, and adverse childhood experiences (ACEs), and protective factors: school belonging, family support, and peer support on both lifetime suicide attempts and past 6-month suicidality in a sample of transgender youth (n = 372). SPSS 22 was utilized to examine the impact of the independent variables on both suicidality and lifetime suicide attempt through two separate logistic regressions. Fifty six percent of youth reported a previous suicide attempt and 86% reported suicidality. Logistic regressions indicated that models for both lifetime suicide attempts and suicidality were significant. Interpersonal microaggressions, made a unique, statistically significant contribution to lifetime suicide attempts and emotional neglect by family approached significance. School belonging, emotional neglect by family, and internalized self-stigma made a unique, statistically significant contribution to past 6-month suicidality. Results have significant practice and policy implications. Findings offer guidance for practitioners working with parents and caregivers of trans youth, as well as, for the creation of practices which foster interpersonal belonging for transgender youth.